Liolaemus cf. elongatus: trauma survival - Avila, Luciano Javier (2012)
The ingestion of unnatural food items can provoke multiple complications in an animal, such as gastrointestinal blockages, perforations, suffocation, and poisoning, often leading to death, but little scientific information is published on this subject. Published accounts on reptiles typically include larger taxa such as turtles, crocodiles, or large-bodied lizards (e.g., Gillett and Jackson 2010. Biawak 4:99–102; Trembath and Freier 2005. Herpetofauna 35:48–49).